Structural performance of seasand recycled aggregate concrete filled Solid/Hollow aluminum tubular Columns: An experimental work. (January 2023) - Fayed, Sabry; Mansour, Walid
Abstract: Seasand recycled aggregate concrete (SRAC) filled solid/hollow aluminum tubular (AT) columns were tested until compression. The investigations were conducted on circular and square specimens. Tests were carried out on unfilled hollow sections (HS), fully filled tubes (FAT) and double-skin tubes, without inner aluminum tube (FHAT), with inner aluminum tube (DSAT) as well as unconfined concrete specimens. Also, mechanical properties of SRAC at 28, 54 and 90 days were investigated. Effect of recycled concrete aggregate content (R), confinement factor, inner void and inner AT on Structural Performance of SRAC-filled ATs is discussed Failure mode, load-shortening/strains relationship, peak load, ductility, stiffness and concrete stress are studied. The results showed R slightly affect mechanical properties of SRAC and had illegible influence on behavior of SRAC-filled ATs. Additionally, AT confinement had a significant effect on ultimate stress in concrete and it clearly improved peak load, ductility, stiffness of SRAC-filled ATs compared to unconfined specimens. Based on present data, proposed equations are derived for estimating normalized strength and normalized shortening/ductility in confined concrete by AT. Also, a proposed formula is modified to be valid for predicting peak load of SRAC-filled ATs.